Accents of English at Czech Schools: Students’ Attitudes and Recognition Skills - Jakšič, Jan; Šturm, Pavel (Research in Language, 2017)
The study investigates the attitudes of 254 Czech students towards English as the main language taught at secondary schools. The questionnaire enquired about their perspectives on learning English in general, British and American cultures and accents of English. Such preferences may have implications for pronunciation model selection in TEFL. In addition, the participants evaluated 12 words pronounced in British or American English for pleasantness, and also assigned them to one of the varieties. Despite the predominance of American culture and despite equal distribution of cultural preferences and equal aesthetic evaluation of the accents, the British variety was marked as more prestigious and was also identified more successfully. Interestingly, the findings differed between students from the capital city and those from regional schools.